Prevalence and clinical relevance of corneal astigmatism in cataract surgery candidates: a southern Italian cohort study - D’Oria, Francesco; Puzo, Pasquale; Nowrouzi, Ali; Boscia, Francesco; Alessio, Giovanni (Frontiers in Medicine, 2026)
BackgroundCorneal astigmatism is a major determinant of visual outcomes after cataract surgery, and its accurate preoperative characterization is essential for surgical planning and toric intraocular lens (IOL) selection. Data from Southern European populations remain limited.MethodsWe conducted a retrospective cohort study including 600 eyes from 306 consecutive cataract patients aged ≥ 40 years undergoing preoperative biometry at a tertiary university hospital in Southern Italy. Axial length (AL), anterior chamber depth (ACD), keratometric power (K), and corneal astigmatism (CA) were measured using partial coherence interferometry.ResultsThe mean patient age was 72.5 ± 8.5 years. The mean AL, ACD, and average K were 23.5 ± 1.6 mm, 3.1 ± 0.5 mm, and 43.9 ± 1.5 D, respectively. The mean CA was 1.02 ± 0.76 D. Notably, 39.8% of eyes had CA ≥ 1.0 D and 9.3% had CA ≥ 2.0 D. Eyes with AL > 26 mm accounted for 7.1% of the cohort.ConclusionA substantial proportion of cataract patients in Southern Italy present with clinically significant corneal astigmatism, highlighting the importance of systematic preoperative screening. These findings support the routine consideration of toric IOLs to optimize refractive outcomes and meet the rising expectations of cataract surgery patients.